Urban Food Sharing - Davies, Anna (Policy Press, 2019)
This book explores the history and current practice of food sharing. Illustrated by rich case studies from around the world, the book uses new empirical data to set an agenda for research and action. The book will be an important resource for researchers, policy makers and sharing innovators to explore the impacts and sustainability potential of such sharing for cities.
Keywords: Food security; Urban food; Food waste; Food sharing; Smart & Sustainable Planet; sustainable food; Attitudes; Community; Environment and housing; Social exclusion; Social participation